A Review on Partial Replacement of Bitumen by Waste Oil, Plastic and Tire In Flexible Pavement - K. Srinivasan; L. Priyadharshini; M. Srividhya; T. Haripiriya; M. Yuvarani (International Journal of Scientific Research in Civil Engineering, 2022)
Around the world Bitumen is defined as a sticky, highly viscous liquid or semi-solid that can be found in some natural deposits or obtained as a by-product of fractional distillation of crude petroleum. It is a key challenge in the highway industry to scale back the dependence on fossil fuels. So, the current challenge for the road industry is to use renewable materials that are bio-materials not subjected to depletion in partial replacement of bitumen, thus making the sector less dependent on petroleum-based products. Waste oil that is disposed of on land or sea without pre-treatment has a negative impact on the environment. Plastic waste refers to the significant amount of plastic that isn’t recycled and ends up in landfills or, in the developing world, is thrown into uncontrolled dump sites. Most tires, especially those fitted to motor vehicles, are manufactured from synthetic rubber. At the same time, the continuous increase in the number of vehicles indicates the need for roads with better quality and engineering design. To reduce the use of non-renewable materials, waste oil, waste plastic and used tyres can be used in their correct ratios to produce partially modified bitumen.